Enculturing sustainable development concept through chemistry curriculum for education for sustainable development - Kanapathy, S. (Springer Nature, 2020)
The enculturation of sustainable development concept through education system, especially via STEM subjects, is vital in developing citizens who are able to adopt sustainability as a life principle. Although STEM agenda has been emphasized in the national education blueprint, attention is needed on the role of STEM education especially chemistry subject toward education for sustainable development. In this chapter, a framework that encompassing six main areas, namely education policy, awareness, resources, curriculum orientation, pedagogical approach and stakeholderâs engagement is proposed in guiding the enculturation of sustainable development concept through chemistry curriculum. The government and institutional policies play an important role to create awareness in understanding the concept and relevance of the sustainable development concept in chemistry subject. Training, finance and time have been identified as resources that need to be considered while integrating sustainable development concept in syllabus and contextualizing chemistry content that should be considered in the curriculum. In addition, the learning outcomes need to be revised based on the pedagogical types, learning approaches and pedagogical techniques used. Lastly, the framework will be instrumental for administrators and teachers to develop a sustainable chemistry teaching toward achieving education for sustainable development with the participation of stakeholders, including government, experts in the field of ESD, administrators and chemistry teachers, in enculturing sustainable development concepts through chemistry subject. Â© 2020, Springer Nature Switzerland AG.